INFLUENCE OF THE ESTIMATION METHOD OF ENERGY-GENERATING EFFICIENCY OF SOLAR CELLS ON THE OPERATIONAL CHARACTERISTICS OF THE SOLAR PANEL - NAKASHYDZE, LILIYA; HILORME, TETIANA (Herald of Khmelnytskyi National University. Technical sciences, 2023)
Currently, solar cells of various types have been developed to operate in different conditions. Preliminary determination of the power generating capacity of solar cells and solar panels is necessary to predict balanced power generation and meet the needs of consumers. Experimental determination of the preliminary operational characteristics of a solar power installation allows solving the problem of uneven energy production. That is, to predict the performance characteristics of solar cells, i.e. the dependence on external factors such as temperature, light level, power surges, etc. Among these factors, the level of illumination is particularly important, since it determines the amount of electricity that a solar cell can generate (the level of generation of the predicted power). It is important to confirm the theoretical calculations that are possible when forming solar panels and pre-selecting solar cells. To address the issue of the efficiency of solar cells and, as a result, the low cost of the generated electricity, it is necessary to optimize the architecture of the solar cell at the design development stage. The following approaches can be used to solve this issue: based on experimental data; based on the construction of an analytical model. The aim of the study is to determine the influence of the method for assessing the energy-generating efficiency of different types of solar cells on the performance characteristics of a solar panel. An analysis of the analytical model of the method for assessing the energy-generating efficiency of different types of solar cells on the performance characteristics of the solar panel was carried out. The approach based on obtaining experimental data during field tests is considered. The performance characteristics of solar cells obtained by analytical and experimental methods are compared. The results obtained on the basis of the above approaches were compared. A comparison of the performance characteristics of solar cells based on solar cells of such types as metal-dielectric-semiconductor with a thin base region, metal-dielectric-semiconductor with a thick base region, and metal-dielectric-semiconductor. It is shown that several factors influence the performance characteristics. Among them are the type of used solar cells and the method of preliminary assessment of their energy-generating efficiency. The data obtained through an automated measuring complex, i.e. on the basis of experimental data, allow us to build polynomial dependencies. This combined approach will allow us to determine the geometric parameters of solar panels with greater accuracy at different levels of energy illumination. The obtained dependencies allow us to calculate the geometric parameters of solar cells for different levels of energy illumination. The dependencies also allow for a comparative analysis of the energy and weight and size parameters of a solar cell (taking into account the type of solar cells used), which are based on such calculations. The use of the obtained results will reduce the weight and dimensions of solar cells, and will significantly reduce the cost of electricity.
Keywords: solar panel; generated energy; hot spot; reliability; service life; technical safety